Natural Compounds Targeting Human Histamine H 1 Receptor For Anti-Allergic Therapy - Jain, Shivangi (My University, 2024)
Background: Allergies, exacerbated by environmental degradation, have a global impact and can pose life-threatening dangers in severe cases. Food allergies, which are an integral part of the "second wave" of the allergy epidemic, can be either IgE or non-IgE mediated. They result in symptoms that affect multiple systems in the body and have a significant impact on millions of people. Earlier antihistamines, such as doxepin, resulted in notable drowsiness and central nervous system (CNS) complications. In response, subsequent antihistamines like cetirizine were created to alleviate these problems, but encountered difficulties nonetheless. The current research is primarily centered around the In-Silico studies with include virtual screening, molecular docking and MD simulation of new natural anti-allergic compounds targeting the human H1 receptor to improve the compatibility and effectiveness of drugs. Results: This in silico study predicts novel natural compounds, silymarin and kenusanone A, as potential antihistamine agents targeting the human histamine H1 receptor. Through a comprehensive virtual screening involving ADMET evaluation, molecular docking, and molecular dynamic simulations, these compounds demonstrated significant binding affinity, stability, and favorable physicochemical properties. The reduced binding free energy and stable protein-ligand interactions suggest their efficacy in inhibiting allergic reactions with minimized side effects. The findings offer valuable insights for the development of safer and more effective antihistamine drugs, leveraging the therapeutic potential of natural compounds.
Keywords: Anti Allergic compounds; virtual screening; molecular dynamic simulation; histamine receptors; DFT; molecular docking; ADMET and PAINS analysis; MMPBSA; molecular dynamic simulation